Altered Onset Response Dynamics in Somatosensory Processing in Autism Spectrum Disorder - Khan, Sheraz; Hashmi, Javeria A.; Mamashli, Fahimeh; Bharadwaj, Hari M.; Ganesan, Santosh; Michmizos, Konstantinos P.; Kitzbichler, Manfred G.; Zetino, Manuel; Garel, Keri-Lee A.; Hämäläinen, Matti S.; Kenet, Tal (Frontiers in Neuroscience, 2016)
Abnormalities in cortical connectivity and evoked responses have been extensively documented in autism spectrum disorder (ASD). However, specific signatures of these cortical abnormalities remain elusive, with data pointing towards abnormal patterns of both increased and reduced response amplitudes and functional connectivity. We have previously proposed, using magnetoencephalography (MEG) data, that apparent inconsistencies in prior studies could be reconciled if functional connectivity in ASD was reduced in the feedback (top-down) direction, but increased in the feedforward (bottom-up) direction. Here, we continue this line of investigation by assessing abnormalities restricted to the onset, feedforward inputs driven, component of the response to vibrotactile stimuli in somatosensory cortex in ASD. Using a novel method that measures the spatio-temporal divergence of cortical activation, we found that relative to typically developing participants, the ASD group was characterized by an increase in the initial onset component of the cortical response, and a faster spread of local activity. Given the early time window, the results could be interpreted as increased thalamocortical feedforward connectivity in ASD, and offer a plausible mechanism for the previously observed increased response variability in ASD, as well as for the commonly observed behaviorally measured tactile processing abnormalities associated with the disorder.